Можливості використання QR-кодів у контексті досягнення цілей маркетингових комунікацій - Балик, У. О.; Колісник, М. В. (Видавництво Львівської політехніки, 2015)
Досліджено питання застосування концепції інтегрованих маркетингових комунікацій у сучасних ринкових умовах. Визначено місце QR-коду в інтегрованих маркетингових комунікаціях, окреслено основні переваги та недоліки його використання, визначено цільову аудиторію користувачів QR-коду. Проаналізовано особливості використання інноваційного медіа-носія QR-коду різними засобами інтегрованих маркетингових комунікацій, визначено формати розміщення повідомлення на носії. The article researches an issue of application of the concept of integrated marketing communications under contemporary market conditions. The author has described a tendency for convergence, which is inherent to modern media channels. Meanwhile, the author has indicated that this process is inherent not only to means used in order to provide a communication process, but also to the sense, which is presented with their help. Moreover, the author has determined a position of a QR-code within the integrated marketing communications, detected the main advantages and disadvantages of its usage, indicated a target audience of QR-code users. The researcher has indicated that a precondition of QR-code emergence was an increasing need of the market for invention of new ways of exchange of greater information amounts, since the information exchange had been earlier performed due to barcoding systems. The author has determined that one of the main causes of increasing popularity of such barcoding systems under modern conditions is more and more expansion of mobile gadgets with increasing technological opportunities. On the basis of analysis of theoretical principles of functioning of two-dimensional barcoding systems such as the QR-system the author has indicated their actions in two directions, i. e. offline- and online-communications. This means that barcoding enables to transform information into a digit form as well as into an inverse form consisting of decoding a script imprinted on a certain surface (a commodity package, a specialized advertising bearer, etc.) into a readable form. An achieved marketing effect is related to an outward appearance of the QR-code and a context appearing in such a case. Thus, the QR-code issue should be considered in the context of visualization. Simultaneously, it should be taken into account that a communication context, presented by the codes, is also of significant importance. The author has determined that the QR-code international standard had been approved in 2004 by the quality management system. In 2011 it was recognized as a standard for mobile phones by the international organization such as Globecomm Systems International. Henceforth, appropriateness of QR-code application has become unquestionable. An evidence of this fact is their widespread application for marketing purposes in enterprises of different sizes, which work in different industries. Furthermore, the author substantiates that nowadays the QR-code can be defined as a representative of modern marketing instruments being a consequence of the scientific and technological progress, which proposes a cheap way of realization of communication between an advertiser and a customer in offline and online modes. On the other hand, taking into account a definition of QR-coding technology as a method of process implementation, the very QR-code should be also considered from the standpoint of their technological content. The author has indicated that the QR-codes are more and more frequently used within large-scale advertising projects in different media channels and information bearers. Their appearance on the web pages is reported to be notable. The author has outlined that application of two-dimensional codes of this type occurs due to an initiative of mobile gadget users. This enables to apply a marketing communication strategy of a “pull” type. Its advantage, in contrast to a “push” strategy, is transmitting an initiative regarding communication process beginning to a customer. Within this context importance of the QRcodes consists of their appropriateness for usage within the marketing communication strategies of the “pull” type, especially on account of possibility of integration of traditional communication means with modern interactive ones and involvement of mobile gadget users in the process of exchange of information with sellers and other users. The author has substantiated that in spite of considerably insignificant application of the QR-codes as equivalents of the barcoding systems in the past, a need for coding, transition, and reading large amounts of information has become a market desire. Consequently, the standardized QR-codes has transformed into many types of two-dimensional coding systems, which are applied depending on market requirements.
QR-code possible usability in the context of achieving marketing communications goals
Keywords: QR-код; маркетингові комунікації; медіа-канали; стратегія; QR-code; marketing communication; media; strategy